TRADISI NGUNJUNG BUYUT NYI MAS ENDANG GEULIS PENGAMPON DESA DANAWINANGUN KECAMATAN KLANGENAN KABUPATEN CIREBON (KAJIAN LIVING HADIS) - Lestari, Dinda; Hartati, Hartati; Iskandar, Amin (Jurnal Studi Hadis Nusantara, 2024)
The tradition of visiting Nyi Mas Endang Geulis' great-grandfather is an annual traditional ceremony held by the Pengampon community of Danawinangun village, Klangenan, Cirebon. This tradition aims to honor and commemorate the services of ancestors, especially Nyi Mas Endang Geulis, who is considered an important figure in local history and culture, by visiting petilasan (a place believed by the community to be the place where Nyi Mas Endang Geulis once visited) to pray for him together. Departing from this background, the researcher was interested in researching more deeply about "how the hadith are lived in the traditional procession of visiting Nyi Mas Endang Geulis Pengampon's great-grandfather". This type of research is field research using qualitative methods and applying living hadith theory. The results of the research show that there is a strong correlation between religion and local culture in the tradition of visiting Nyi Mas Endang Geulis' great-grandfather. This can be seen in the process, which from start to finish never lets go of reciting dhikr and prayer. The dhikr and prayers that are read during the procession are First, the Prophet's prayers which refer to the hadith of the Prophet narrated by Imam Nasa'i, number 1292 regarding the recommendation of reading the Prophet's prayers and the hadith narrated by Imam Tirmidhi, number 486 and 484 about the virtues of reading the Prophet's prayers. Second, do tawassul, tahlilan and prayer together, referring to the hadith of the Prophet in Muslim history, number 1631 regarding practices that can reach the deceased after death. Third, displaying heirlooms while accompanied by chanting the phrase lÄilÄha illallah, referring to the hadith of the Prophet narrated by Imam Ibn Majah, number 3800 regarding the virtues of people who read tahmid.